The role of dendritic cells the in development of atherosclerosis of coronary vessels in the experiment. - Tryasak, N. S. (Medicni Perspektivi, 2018)
The dynamics of quantitative and qualitative changes of the dendritic cells (DC) of coronary arteries wall at different stages of atherosclerosis development was investigated. Animals received human native low density lipoproteins. Dendritic cells were detected by using polyclonal antibodies S-100 and monoclonal antibodies CD1a (clone O10). A semiquantitative scale from 0 to 3 points was used to determine the intensity of expression of immunohistochemical markers. Histological examination of coronary arteries wall was perfomed by hemothoxylin-eosin, orsein andsudanIII. The first increase of the number of dendritic cells was observed at the 10th week after start of experiment, which corresponded to prelipid stage of atherosclerosis. The second increase of the number of dendritic cells was noted at the 13week and was characterized by moderate expression of markers (2 points) and morphologically responded to the stage of lipoidosis. The late stages of the experiment (18-20 week) were characterized by the maximal increase of DC and a high expression of immunohistochemical markers (3 points).